Literature Review : Gambaran Efektivitas Pemeriksaan Keracunan Merkuri Dengan Sampel Biologis: Literature Review : Description of the Effevtiveness of Mercury Poisoning Examination Using Biological Sample - Sinaga, Hakim; Wahid, Rifky Saldi A.; Raudah, Siti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Mercury is one of the heavy metals with high toxicity and is included in the class of neurotoxic substances that can cause various damage to tissue and nerve cells. The proper use of biomarkers in blood, urine and hair can determine the effectiveness of the mercury poisoning examination in the laboratory. Purpose: This study aimed to describe the effectiveness of mercury poisoning examination using biological samples. Method: This study used a literature review with online database sources from the search engine Science Direct, PubMed, Google Scholar. Result, The cause of mercury poisoning was through the use of mercury in various industrial fields, mining activities, consumption of fish, shellfish and water that had been contaminated with mercury. Examination of mercury poisoning with blood and urine biomarkers was the main choice for acute exposure due to the direct use of mercury, especially in the work environment. Hair biomarkers were the main choice for chronic exposure, mainly fish consumption. The length of working time and the frequency of fish consumption had a significant influence on the high levels of mercury in the body, where the longer and more mercury exposure, the more risk a person was to experience mercury poisoning. Mercury levels in the blood can be detected within 2-3 days, in urine one week after exposure, and in hair, levels are persistent in the long term. Conclusion: The effectiveness of mercury poisoning examination using biological samples depends on the type and duration of exposure, where short-term exposure to high concentrations uses blood and urine biomarkers and long-term exposure using hair biomarkers.